Nutlin-3 sensitizes nasopharyngeal carcinoma cells to cisplatin-induced cytotoxicity - Voon, Y.L.; Ahmad, M.; Wong, P.F.; Husaini, R.; Ng, W.T.W.; Leong, C.O.; Lane, D.P.; Khoo, A.S.B. (Spandidos Publications, 2015)
The small-molecule inhibitor of p53-Mdm2 interaction, Nutlin-3, is known to be effective against cancers expressing wild-type (wt) p53. p53 mutations are rare in nasopharyngeal carcinoma (NPC), hence targeting disruption of p53-Mdm2 interaction to reactivate p53 may offer a promising therapeutic strategy for NPC. In the present study, the effects of Nutlin-3 alone or in combination with cisplatin, a standard chemotherapeutic agent, were tested on C666-1 cells, an Epstein-Barr virus (EBV)-positive NPC cell line bearing wt p53. Treatment with Nutlin-3 activated the p53 pathway and sensitized NPC cells to the cytotoxic effects of cisplatin. The combined treatment also markedly suppressed soft agar colony growth formation and increased apoptosis of NPC cells. The effect of Nutlin-3 on NPC cells was inhibited by knockdown of p53, suggesting that its effect was p53-dependent. Extended treatment with increasing concentrations of Nutlin-3 did not result in emergence of p53 mutations in the C666-1 cells. Collectively, the present study revealed supportive evidence of the effectiveness of combining cisplatin and Nutlin-3 as a potential therapy against NPC.